1997
DOI: 10.1007/978-1-349-25562-7
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Careers and Organisations

Abstract: Any person who does any unauthorised act in relation to this publication may be liable to criminal prosecution and civil claims for damages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
129
0
12

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 307 publications
(146 citation statements)
references
References 0 publications
5
129
0
12
Order By: Relevance
“…Indeed, a recent British study has suggested that although women are no longer the focus of direct exclusionary practices within the workplace, in career terms, a new division is opening up within organisations; between 'encumbered' and 'unencumbered' workers -that is, those with and without caring responsibilities (Halford et al 1997). Does this mean that current exhortations to employers (for example, by the British Government) to enhance the extent of their 'family friendliness' will prove to be, in the last analysis, relatively meaningless?…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a recent British study has suggested that although women are no longer the focus of direct exclusionary practices within the workplace, in career terms, a new division is opening up within organisations; between 'encumbered' and 'unencumbered' workers -that is, those with and without caring responsibilities (Halford et al 1997). Does this mean that current exhortations to employers (for example, by the British Government) to enhance the extent of their 'family friendliness' will prove to be, in the last analysis, relatively meaningless?…”
Section: Introductionmentioning
confidence: 99%
“…In Britain, the implications of such developments for the professional work of nurses, midwives and doctors are reported to include increased conflict and uncertainty concerning professional boundaries. [9][10][11][12] Although one panacea would include a more egalitarian professionalism, 3,10, 13 Degeling et al have argued that doctors' individualistic attitudes to their work make them less supportive of teamwork than nursing colleagues and managers. 1 Such underlying tensions have not been widely examined in maternity settings, yet lively public controversies about the appropriate "social design" of birth impact directly on organisational and professional arrangements.…”
mentioning
confidence: 99%
“…The attempt to 'embody' labour has not, however, yet told us as much about the relation between bodies in the workplace. While there is research on the embodied relations between workmates or members of organisations (which features in Halford et al (1997) and other research on gendered organisations), this is rarely extended to explore embodied relations between workers and the customers, clients and patients with, and on whom, they work. In looking at the interaction between workers' and these bodies-worked-upon, including the ways in which this interaction is sexualised or desexualised, we need to consider the role of customers, clients and patients as embodied, wilful subjects, and at how their bodily vulnerability, variability, and unpredictability affects the organisation of the work and workers' relation to the labour process, along with the sensory nature of this relationship, which (as evocatively evidenced by Cheung, this volume) involves touch, taste and smell as well as visual and aural interaction.…”
Section: Conceptualising Body/sex Workmentioning
confidence: 99%